2015
DOI: 10.1007/s10637-015-0218-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of the sachet formulation of the oral dual PI3K/mTOR inhibitor BEZ235 given twice daily (BID) in patients with advanced solid tumors

Abstract: Introduction The PI3 kinase (PI3K) pathway is a commonly dysregulated pathway in cancers and is an attractive target for antitumor therapy. BEZ235 is a potent, highly specific and selective dual PI3K/mTOR inhibitor. Methods Patients were enrolled in a 3 + 3 dose escalation design to determine the maximum tolerated dose (MTD), toxicities, and pharmacokinetics (PK) of BEZ235 when administered twice-daily as an oral sachet. For intrapatient PK comparison, patients were to receive a lead in of the total daily dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 14 publications
4
60
0
Order By: Relevance
“…Conventional cancer treatment utilizes chemotherapy at the maximally tolerated dose (MTD), or the highest dose shown to be both cytotoxic and tolerable for the patient. Clinical studies including trials of dactolisib alone in pancreatic neuroendocrine tumors (70) and bladder cancers (71) showed that dactolisib was poorly tolerated as the MTD was 300 mg in the phase I study (72). These studies did demonstrate limited clinical efficacy with several patients with stable disease but given the poor tolerability, these trials did not advance.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional cancer treatment utilizes chemotherapy at the maximally tolerated dose (MTD), or the highest dose shown to be both cytotoxic and tolerable for the patient. Clinical studies including trials of dactolisib alone in pancreatic neuroendocrine tumors (70) and bladder cancers (71) showed that dactolisib was poorly tolerated as the MTD was 300 mg in the phase I study (72). These studies did demonstrate limited clinical efficacy with several patients with stable disease but given the poor tolerability, these trials did not advance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Choi and colleagues used PI-103, a novel of PI3Kα and mTOR dual inhibitor, showed that treatment with PI-103 increased the cytotoxic effect of radiation therapy plus TMZ in U251 cells [32]. NVP-BEZ235 has shown great promise in controlling solid tumors in preclinical mouse models [33] and has been reported to increase sensitivity to radiotherapy [15,23] and gefitinib [34]. To our knowledge, effects of NVP-BEZ235 on the cytotoxicity of TMZ have not been studied in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mucositis is also one of the main dose-limiting toxicities of the TORKi compounds (Table S1) AZD2014 (Basu et al, 2015) and CC-223 (Bendell et al, 2015a), and occurred frequently in a phase I trial of TAK-228 (Ghobrial et al, 2016). Mucositis was reported in phase I studies of pan-PI3K inhibitor buparlisib (BKM120) (Bendell et al, 2012; Ragon et al, 2017) and the dual PI3K/mTOR inhibitor BEZ235 (Bendell et al, 2015b; Carlo et al, 2016). The p110δ inhibitor idelalisib is associated with autoimmune colitis as discussed below, but also with lung and liver inflammation (Coutré et al, 2015) that might arise from increased innate immune stimulation.…”
Section: Pi3k In Innate and Adaptive Immunitymentioning
confidence: 99%